Tetra(tien-2-il)porfirina e seus complexos com metais da primeira-série de transição: síntese, caracterização, investigação da citotoxicidade e interação com DNA - Pereira, George Bueno Santana (Universidade Federal de São Carlos, 2020)
Cancer is a generic term for over 100 diseases with uncontrolled cell growth. Each year, all cancer forms are responsible for millions of deaths worldwide and are the leading cause of deaths linked to disease. Therefore, the scientific community is searching for new compounds that serve as agents for chemotherapy. However, there has been a promising application of metalloporphyrins, as these substances have planar structures that interact intermolecularly with DNA molecule. Incorporation of transition metals can increase the solubility and planarity of this class of compounds, enabling different forms of interaction with the DNA double-strand. It is known that 5,10,15,20-tetra- (thien-2-yl) -21H, 23H-porphyrin (H2TTP) contains substituents in a meso position almost coplanar to the porphyrin ring, providing greater planarity when compared to meso-substituted analog compounds. Thus, in this work, porphyrinic complexes of zinc(II), nickel(II), cobalt(II), copper(II), and manganese(III) were synthesized using H2TTP as a ligand. The compounds were characterized by spectroscopic techniques such as UV-vis, Infrared, fluorescence, and 1H NMR, as well as HRMS-ESI, molecular conductivity and elementary analysis. Data from spectroscopy in the UV-vis region showed that all complexes were able to interact with ct-DNA, obtaining a binding constant in the order of 105 M-1, indicating a non-covalent interaction. Changes in the electrophoretic mobility of the plasmid pBR322 were also observed after incubation (24h) with the [Mn(TTP)Cl] complex. Cytotoxicity of all compounds were evaluated towards two cell lines, A2780cis (cisplatin-resistant ovarian tumor) and DU-145 (prostate tumor). It has been confirmed that the [Mn(TTP)Cl] complex was active against both cell lines, A2780cis (IC50 = 3.45 ± 0.14 μmol.L-1) and DU-145 (5.28 ± 0.23 μmol.L-1) were more cytotoxic than cisplatin. However much, the other complexes did not demonstrate activity in concentrations at 50 μmol.L-1 or lowest. Analyzing the results, it can be concluded that DNA is not the key target involved in [Mn(TTP)Cl] complex cytotoxicity, which further opens up greater possibilities for biological investigation.
Tetra(thien-2-yl)porphyrin and their complexes with first transition series metals: synthesis, characterization, cytotoxicity investigation, and interaction with DNA
Keywords: Síntese; Caracterização; Porfirina; Complexo; Citotoxicidade; Interação com DNA; Synthesis; Characterization; Porphyrin; Complex; Cytotoxicity; DNA interaction; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::DETERMINACAO DE ESTRUTURA DE COMPOSTOS INORGANICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA